Peningkatan Kemampuan Komunikasi Bisnis Berbasis Visual Era Digital Untuk Usaha Kecil Kerajinan Di Kota Malang - Dewantara, Rizki Yudhi; Afrianty, Tri Wulida; Pangestuti, Edriana; Susilo, Heru (ISAS (Indonesian Society of Applied Science), 2022)
The use of video editing applications for business products that are used as business communication in the use of social media such as Facebook, Instagram, and marketplaces has been widely used by the public. Community Service activity seeks to provide deeper knowledge about the use of simple video making applications that have more positive meaning for all elements of society. The target members of this activity are small craft businesses and the members of a small business group in Malang City. Based on identification of the problem, found that small entrepreneurs have difficulty competing in visual marketing with medium and large entrepreneurs who have strong resources in funding. This activity is carried out starting from problem identification, visualization-based digital marketing socialization, as well as training and assistance in making simple product videos, implementing effective activities starting from August to November 2021. The result of this activity is the acceptance of knowledge transfer from academics to the community, especially small businesses. Implementing activities are lecturers assisted by students and practitioners in the field of visual communication.